2022
DOI: 10.3389/fmed.2022.817127
|View full text |Cite
|
Sign up to set email alerts
|

Early Estimated Glomerular Filtration Rate Trajectories After Kidney Transplant Biopsy as a Surrogate Endpoint for Graft Survival in Late Antibody-Mediated Rejection

Abstract: BackgroundLate antibody-mediated rejection (ABMR) after kidney transplantation is a major cause of long-term allograft loss with currently no proven treatment strategy. Design for trials testing treatment for late ABMR poses a major challenge as hard clinical endpoints require large sample sizes. We performed a retrospective cohort study applying commonly used selection criteria to evaluate the slope of the estimated glomerular filtration rate (eGFR) within an early and short timeframe after biopsy as a surrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Our approach, which involved the use of linear mixed models incorporating a substantial number of creatinine measurements (a median of 49 measurements per patient), allowed us to examine associations for both baseline eGFR and eGFR slopes. In line with previous research [4,8], we observed a significant decline in renal functional following ABMR diagnosis, with an average eGFR slope of −5.4 mL/min/1.73 m [2] per year. Through this detailed examination of the eGFR course, we were able to distinguish between processes contributing to the dynamic progression of graft dysfunction, which might be amenable to intervention, and processes related to the irreversible loss of nephrons.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our approach, which involved the use of linear mixed models incorporating a substantial number of creatinine measurements (a median of 49 measurements per patient), allowed us to examine associations for both baseline eGFR and eGFR slopes. In line with previous research [4,8], we observed a significant decline in renal functional following ABMR diagnosis, with an average eGFR slope of −5.4 mL/min/1.73 m [2] per year. Through this detailed examination of the eGFR course, we were able to distinguish between processes contributing to the dynamic progression of graft dysfunction, which might be amenable to intervention, and processes related to the irreversible loss of nephrons.…”
Section: Discussionsupporting
confidence: 92%
“…Our present study aimed to address this gap and provide additional insights into the relationship between IRRAT score and both the baseline eGFR and its slope. Previous studies have demonstrated a close association between the eGFR slope in ABMR, serving as a potentially valuable surrogate endpoint, and long-term graft survival [ 4 , 8 ]. As expected, our mixed model analysis revealed associations between IRRAT score and baseline eGFR, and univariable Cox regression demonstrated a strong association between IRRAT score and graft loss (2.7-fold risk; p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the effect of treatment modification on hard outcomes, such as kidney failure with replacement therapy, we selected the eGFR slope among various surrogate endpoints, instead of albuminuria change, since urinary protein was negative in most KTRs, except for those with recurrent nephritis. Moreover, the association between graft outcome and eGFR slope for at least 12 months after biopsy has been confirmed recently in KTRs [ 16 ]. This result supports the validity of eGFR slope as a surrogate endpoint for graft survival.…”
Section: Discussionmentioning
confidence: 88%